2012
DOI: 10.1590/s1415-47572012005000029
|View full text |Cite
|
Sign up to set email alerts
|

Association of the TCF7L2 rs12255372 (G/T) variant with type 2 diabetes mellitus in an Iranian population

Abstract: In various populations worldwide, common variants of the TCF7L2 (Transcription factor 7-like 2) gene are associated with the risk of type 2 diabetes mellitus (T2DM). The aim was to investigate the association between rs12255372 (G/T) polymorphism in the TCF7L2 gene and T2DM in an Iranian population. 236 unrelated patients with T2DM, and 255 normoglycemic controls without diabetes were studied. The PCR-RFLP method was used for genotyping rs12255372 (G/T) polymorphism, and the SPSS version 18.0 for Windows for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 32 publications
7
14
0
Order By: Relevance
“…Of 31 provinces in Iran, studies on only two provinces, Gorgan 50 and Kurdish, 51 revealed that the frequency of the TCF7L2 rs7903146 polymorphism was significant, which is in agreement with present study. In contrast to our study, a lack of remarkable association between TCF7L2 rs7903146 polymorphism and T2D was reported among the Arabian Emirates 52 and Saudi Arab population.…”
Section: Discussionsupporting
confidence: 92%
“…Of 31 provinces in Iran, studies on only two provinces, Gorgan 50 and Kurdish, 51 revealed that the frequency of the TCF7L2 rs7903146 polymorphism was significant, which is in agreement with present study. In contrast to our study, a lack of remarkable association between TCF7L2 rs7903146 polymorphism and T2D was reported among the Arabian Emirates 52 and Saudi Arab population.…”
Section: Discussionsupporting
confidence: 92%
“…However no data from Iranian population as a type of Asian population was included in this meta-analysis [ 111 ]. In line with these data, in our study, we found a positive association between rs12255372 and rs7903146 variants of TCF7L2 and T2DM [ 38 , 48 , 53 ].…”
Section: Discussionsupporting
confidence: 90%
“…Association between two polymorphisms of TCF7L2 including rs7903146 (C/T) and rs12255372 (G/T) was assessed in three studies [ 38 , 48 , 53 ]. In one study investigating rs7903146 (C/T) in 466 subjects, significant difference in the frequency of CC and CT genotypes was observed between T2DM and control group ( P = 0.045) [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These three SNPs, individually and/or as a group, were found to be associated with T2DM in a wide spectrum of world populations: Finnish [19], Amish [20], U.S [21], Polish [22], Scandinavian [23], Chinese [24], Brazil [25], Japanese[26][28], Swedish [29], U.K [30], Dutch [31], Palestinian [32], Iranian [33], [34], Arab [35], Tunisian [36], Persian [37] as well as Indian populations [13][17]. Of the three SNPs, rs7903146 is the most consistent in several GWAS studies [5], [38][45] as well as most replicated variant of TCF7L2.…”
Section: Introductionmentioning
confidence: 99%